2004
DOI: 10.1645/ge-188r
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Anisakis Simplex (Nematoda) in Harbor Porpoises Phocoena Phocoena Off Denmark

Abstract: The population structure and habitat selection of Anisakis simplex in 35 harbor porpoises off Denmark are described. The nematodes were collected from the stomach and duodenal ampulla and were categorized as third-stage larvae, fourth-stage larvae, subadults, and adults. The porpoises harbored 8,043 specimens of A. simplex. The proportion of adults and subadults increased with infrapopulation size. The number of development stages across infrapopulations covaried significantly (Kendall's test of concordance). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The life cycles of these nematodes are similar and involve crustaceans and many species of fish that serve as intermediate or paratenic hosts, with marine mammals as the final hosts (McClelland et al , 1990). Important cetacean hosts for A. simplex that are also reported in the Baltic Sea are the harbour porpoise, Phocoena phocoena (Herreras et al , 2004), the white-beaked dolphin, Lagenorhynchus albirostris , and the common bottlenose dolphin Tursiops truncatus (Smith & Wootten, 1978). The grey seal, Halichoerus grypus , is considered to be the most important final host for C. osculatum (Fagerholm, 1990), and the common seal (harbour seal), Phoca vitulina , is the most important final host for P. decipiens (Aspholm et al , 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The life cycles of these nematodes are similar and involve crustaceans and many species of fish that serve as intermediate or paratenic hosts, with marine mammals as the final hosts (McClelland et al , 1990). Important cetacean hosts for A. simplex that are also reported in the Baltic Sea are the harbour porpoise, Phocoena phocoena (Herreras et al , 2004), the white-beaked dolphin, Lagenorhynchus albirostris , and the common bottlenose dolphin Tursiops truncatus (Smith & Wootten, 1978). The grey seal, Halichoerus grypus , is considered to be the most important final host for C. osculatum (Fagerholm, 1990), and the common seal (harbour seal), Phoca vitulina , is the most important final host for P. decipiens (Aspholm et al , 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The main final hosts for A. simplex in the Baltic Sea are cetaceans, namely the harbour porpoise, P. phocoena (Herreras et al ., 2004), the white-beaked dolphin, L. albirostris , and the common bottlenose dolphin, T. truncatus (Smith and Wootten, 1978). The density and distribution of harbour porpoise in the central Baltic Sea or Baltic Proper considerably declined during the last century (Koschinski, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The life cycles of A. simplex , C. osculatum and P. decipiens are similar and involve marine mammals as the final hosts (McClelland et al ., 1990; Klimpel and Palm, 2011). The following important cetacean hosts for A. simplex have also been reported in the Baltic: the harbour porpoise, Phocoena phocoena (Herreras et al ., 2004), the white-beaked dolphin, Lagenorhynchus albirostris , and the common bottlenose dolphin Tursiops truncatus (Smith and Wootten, 1978). According to Fagerholm (1990), the grey seal, Halichoerus grypus , is considered to be the most important final host for C. osculatum , while the common seal (harbour seal), Phoca vitulina , is the most important final host for P. decipiens (Aspholm et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…in strandings of harbour porpoise (60%), common dolphin (71%) and white-beaked dolphin (5 out of 6 individuals) in England. Herreras et al (2004) found an average intensity of 230 Anisakis simplex in 35 harbour porpoise sampled in Denmark. The fact that the abundance of porpoise and minke whale is higher in the North Sea than on the west coast of Scotland (Hammond et al, 2013) may thus help explain the difference in infection rates in fish.…”
Section: Spatial and Seasonal Patterns In Infection Ratementioning
confidence: 91%